Pengelolaan Program Pendidikan Nonformal untuk Kelompok Masyarakat Lanjut Usia - Irmawita, Irmawita (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2018)
The essence of national development is to build on a solid foundation and strong foundation in the form of certain conditions in various national life. Community development there are two challenges that need to be considered to build the organization (organization development) and economic development (economic development). In the development of organizations, the organization is the frame work of every form of cooperation to achieve a common goal, therefore it needs to be built on the basis of a democratic, dynamic and harmonious relationship. Likewise with the elderly community groups, based on Boyle's taxonomic thinking about the type of non-formal education is divided into three types: developmental, institutional, and informational. Developmental programs are also called community development programs, where the main program objectives are solving social, economic, cultural, political, and defense and security problems facing the target group through action programs. An instituional program is also called a training program aimed at mastering a set of capabilities (knowledge, attitudes and / or skills) by the target group. While the informational program can be called also with counseling or publicity, aims to achieve a set of information by the target group. Thus the community development program is one of the types of non-formal education programs.